2020
DOI: 10.1002/aoc.6105
|View full text |Cite
|
Sign up to set email alerts
|

Ir(triscarbene)‐catalyzed sustainable transfer hydrogenation of levulinic acid to γ‐valerolactone

Abstract: Sustainable iridium‐catalyzed transfer hydrogenation using glycerol as the hydride source was employed to convert levulinic acid to γ‐valerolactone (GVL) with exceptionally high turnover numbers (TONs) (500,000) and turnover frequencies (TOFs) (170,000 h−1). The highly efficient triscarbene‐modified iridium catalysts demonstrated good catalytic activities with low catalyst loadings (0.7 ppm) and good recyclability with an accumulated TON of over two million in the fourth reaction. In addition to glycerol, prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 37 publications
(49 reference statements)
0
4
0
Order By: Relevance
“…Glycols are also candidates with great potential for transfer hydrogenation. Sung et al (2020) probed triscarbene-modified iridium catalysts for the LA CTHC using glycerol (G), propylene glycol (PG), ethylene glycol (EG), isopropanol (IPA), and ethanol (EtOH) with resulting turnover numbers of 500,000 (G), 339,000 (PG), 242,000 (EG), 334,000 (IPA), and 208,000 (EtOH), respectively (Sung et al 2020). Nevertheless, yields are less than 70%, so this field has to be further explored.…”
Section: Solventmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycols are also candidates with great potential for transfer hydrogenation. Sung et al (2020) probed triscarbene-modified iridium catalysts for the LA CTHC using glycerol (G), propylene glycol (PG), ethylene glycol (EG), isopropanol (IPA), and ethanol (EtOH) with resulting turnover numbers of 500,000 (G), 339,000 (PG), 242,000 (EG), 334,000 (IPA), and 208,000 (EtOH), respectively (Sung et al 2020). Nevertheless, yields are less than 70%, so this field has to be further explored.…”
Section: Solventmentioning
confidence: 99%
“…The Lewis acid sites (electron acceptors) catalyze the hydrogenation of the gamma hydroxyl of LE to obtain the 4-hydroxy-levulinate, whereas the acidic Brønsted sites (proton H + donor) catalyze the subsequent intraesterification to GVL (Hengne et al 2016). It has been proposed that acidic and basic sites in the catalyst play a synergistic role (Xie et al 2016;Sung et al 2020;Vasanthakumar et al 2020;Yu et al 2020b;Wan et al 2021). Wan et al (2021) proposed that the Lewis acidity of the metal cation Zr +4 contributes to the activation of the LA carbonyl group, whereas the basic O -2 produces the disaggregation of the hydroxyl groups in IPA, and these effects should significantly accelerate the CTH reaction (Wan et al 2021).…”
Section: Catalystmentioning
confidence: 99%
“…27 Jang et al also reported an Ir(triscarbene) catalyst ( 7 in Scheme 1) for transfer hydrogenation of LA to GVL in water at 150 °C using glycerol as a hydrogen source in the presence of Ba(OH) 2 and observed an appreciably high TON of 500 000. 28 Recently, Tu et al used the self-supporting strategy and reported a solid molecular catalyst based on bis-N-heterocyclic-carbene-iridium complexes for LA to GVL conversion at 100 °C and 1 bar H 2 . 29 Although, Ir based molecular catalysts are reported to be more active and display a higher TOF than Ru based catalysts, the Ru catalysts have relatively low cost and easy availability and thus used more widely at laboratory and industrial scales.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the reducing nature of glucose makes its disproportionation easy under the reported CTH reaction conditions. , Enhancing the productivity of glucose to sorbitol CTH requires using hydrogen donors from which hydrogen abstraction is easier as compared to glucose or at least using reaction conditions favoring so. Most of the reported hydrogen donors in biomass valorization include sacrificial alcohols, formic acid and its esters, , cyclic ethers and amines, or glycerol. , On the contrary, the use of diols, despite their good performance as hydrogen donors with their dehydrogenation being coupled with some interesting hydrogenation reactions, has been barely used in biomass valorization. One of the few examples is the work of Pérez-Ramírez et al .…”
Section: Introductionmentioning
confidence: 99%